2017
DOI: 10.1093/jpids/pix079
|View full text |Cite
|
Sign up to set email alerts
|

Immunization Completion in Infants Born at Low Birth Weight

Abstract: After adjustment for preterm birth, comorbid neonatal conditions, and early childhood patterns of healthcare use, LBW was significantly associated with immunization noncompletion in a universal healthcare system. Provider consistency and well-child care seem important for increasing immunization completion in LBW infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
0
16
2
Order By: Relevance
“…13 Authors of a more recent study conducted in the military health care system demonstrated that infants with low birth weight and preterm infants, identified by using International Classification of Diseases, Ninth Revision codes, had lower odds of vaccine receipt by 24 months of age. 11 In the current study, preterm infants did not catch up to term/ postterm infants by 36 months of age. Authors of an earlier study reported that differences in up-to-date vaccination status by birth weight remained over time, 14 whereas authors of other studies observed a persistent discrepancy only among infants with extremely low birth weight.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…13 Authors of a more recent study conducted in the military health care system demonstrated that infants with low birth weight and preterm infants, identified by using International Classification of Diseases, Ninth Revision codes, had lower odds of vaccine receipt by 24 months of age. 11 In the current study, preterm infants did not catch up to term/ postterm infants by 36 months of age. Authors of an earlier study reported that differences in up-to-date vaccination status by birth weight remained over time, 14 whereas authors of other studies observed a persistent discrepancy only among infants with extremely low birth weight.…”
Section: Discussioncontrasting
confidence: 48%
“…These findings extend previous work indicating undervaccination among not only the highest-risk infants but also infants born with a low birth weight or infants born moderately to late preterm. 11,14 In our study, these preterm groups had comparably low coverage levels for most individual vaccines, except rotavirus, hepatitis B, and influenza vaccines. Lower rotavirus vaccination coverage among early preterm infants likely reflects the ACIP recommendation to delay receipt of the first dose until hospital discharge.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…26 Nestander et al showed immunization completion to be significantly decreased at 24 months in LBW infants. 30 Hofstetter et al found preterm infants less likely to have completed all doses of the "7-vaccine series" by age the age of 19 months. 51 The finding that preterm infants have completed catch up at 24 months in Israel may be attributed to the organization of provision of vaccination and accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…Medical conditions associated with preterm birth such as chronic lung disease and health provider change have also been associated with immunization non-completion. [26][27][28][29][30][31][32] Targeted preterm vaccination intervention programs have reported favorable results in Ireland and Italy. 33,34 Delay of vaccination in preterm and LBW infants may most likely stem from inappropriate knowledge and perceptions of both parents and health-care providers regarding the safety and efficacy of timely routine childhood vaccinations.…”
Section: Introductionmentioning
confidence: 99%